Museums and Crisis Management due to Covid -19. Effects of Pandemic and the Role of Digital and Social Networks Communication - Marzano, Marianna; Castellini, Monia (European Scientific Journal, ESJ, 2022)
The overall purpose of this study is the effects of lockdown within Italian museums caused by the Coronavirus disease-19 (Covid-19) emergency. During the pandemic, the museums are being closed, and the use of digital content and social networks seems to have been the solution to overcome the closure problem. The study analyzes the role of digital content and tools in communication to manage the shock due to Covid-19. The basic design of the research recurs to the crisis management model used to analyze three stages crossed by museums as preparedness, reaction, and recovery. The study involved several Italian museums grouped according to the art collection, governance, and funding sources. A semi-structured questionnaire was sent to them. The main findings show the presence of digital as a strategy already adopted by museums before the outbreak. However, the results reveal the absence of a preventive phase as requested by the model of crisis management. At the same time, it has emerged the need to adapt the digital content to guarantee the mission of fruition for the public.